2023
DOI: 10.5056/jnm22037
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Irritable Bowel Syndrome in Japan, China, and South Korea: An International Cross-sectional Study

Abstract: Background/AimsSymptoms of irritable bowel syndrome (IBS), a common gut-brain interaction disorder, deteriorate patients' quality of life and increase medical needs; therefore, IBS represents a significant global burden. The estimated global prevalence is approximately 10%; however, accumulated evidence shows international heterogeneity. In this study, we have described and compared the prevalence of IBS in 3 East Asian countries: Japan (Tokyo and Fukuoka), China (Beijing), and South Korea (Seoul). MethodsWe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…However, the prevalence substantially varied between countries worldwide, and the reason still needs to be identified [ 2 ]. A 2023 study reported that the prevalence from Japan, China, and South Korea was reported as 14.9%, 5.5%, and 15.6%, respectively, with a 54.9% male population [ 48 ]. An SR by Al-baghli et al based on Saudi studies reported that the IBS prevalence ranged from 7.9% to 40.7% [ 49 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the prevalence substantially varied between countries worldwide, and the reason still needs to be identified [ 2 ]. A 2023 study reported that the prevalence from Japan, China, and South Korea was reported as 14.9%, 5.5%, and 15.6%, respectively, with a 54.9% male population [ 48 ]. An SR by Al-baghli et al based on Saudi studies reported that the IBS prevalence ranged from 7.9% to 40.7% [ 49 ].…”
Section: Reviewmentioning
confidence: 99%
“…The 38 studies were based on both-gender, male-only, and female-only studies. Nevertheless, the gender predominance is still not concluded [ 47 , 48 ]; however, a higher prevalence was reported for females [ 3 ].…”
Section: Reviewmentioning
confidence: 99%
“…With the changing times, the burden of life and work has increased, and the diets and rest patterns of individuals have become extremely irregular, which can easily induce IBS. A recent international cross-sectional study reported that the overall prevalence of IBS in East Asia was 12.6% [ 6 ]. Although IBS is not fatal, it seriously affects health and quality of life and imposes a heavy financial burden on families and social healthcare [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1 The overall prevalence of IBS in a recent study in East Asia, including Japan, China, and South Korea, using Rome III criteria was slightly higher than the global prevalence, and male patients comprised 54.9% of the cases. 2 IBS is associated with a significant financial burden on healthcare and adversely affects patients’ quality of life. 3 With these challenges, there is an urgent need to develop and implement novel IBS drugs.…”
mentioning
confidence: 99%